S-type heterojunction photocatalyst as well as preparation method and application thereof
Prepare ZN0.5CD0.5S/G-C3N4 S-type heterogeneous optical catalysts through thermal reduction technology and in-situ synthesis method, solving the problem of low response ability of the existing photocatalyst at visible light and poor chemical stability, and realized efficient efficiency Optical activity and chemical stability are suitable for applications such as CO2 restore and Sipstone degradation.
Patent Information
- Application Number
- CN202411553352.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-01-28
Smart Images

Figure CN119368217A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nanocomposite materials, and particularly relates to an S-type heterojunction photocatalyst and a preparation method and application thereof. Background Art
[0002] Semiconductor photocatalysts are a class of materials that can generate electrons and holes through light excitation, thereby promoting chemical reactions. These materials have shown broad application prospects in environmental governance, renewable energy, and catalytic reactions. Currently, semiconductor photocatalysts used to activate peroxydisulfate (PDS) under visible light usually have disadvantages such as low response to visible light, fast recombination rate of photogenerated carriers, and poor chemical stability. Therefore, designing new and efficient photocatalysts has been a research hotspot in recent years.
[0003] g-C3N4 is an emerging metal-free polymer semiconductor with the advantages of suitable band structure, stable chemical properties and environmental friendliness. It has great potential in the field of photocatalysis. However, pure g-C3N4 has disadvantages such as low specific surface area and rapid recombination of photogenerated electron-hole pairs, which makes it impossible to be effectively applied. In addition, among many bimetallic sulfides, ZCS is considered to be an efficient photocatalytic material due to its strong response to visible light and adjustable band gap. However, ZCS is prone to photocorrosion, resulting in poor chemical stability of the photocatalyst. In summary, given that g-C3N4 has highly uniform nitrogen ligands, it can provide abundant lone pairs of electrons to capture Zn in ZCS. 2+ and Cd 2+ , thereby obtaining an efficient and stable heterojunction.
[0004] Chinese patent application number 202210916275.4 discloses a Zn x Cd 1-x S / g-C3N4 sheet composite S-type heterojunction photocatalyst, preparation method thereof and application thereof in the field of photocatalytic carbon dioxide reduction. Zn x Cd 1-x S nanosheets were loaded on the surface of g-C3N4 by in-situ growth; the Zn / Cd ratio was changed to x Cd 1-x The band structure of S was precisely controlled, and a composite S-type heterostructure was successfully constructed. The ultra-thin g-C3N4 sheet has a more negative conduction band potential and stronger CO2 adsorption capacity. x Cd 1-x S can improve the light harvesting ability in the visible light range. x Cd 1-xBased on the advantages of S, the composite structure of sheets can effectively shorten the carrier transmission path, improve the separation efficiency of photogenerated electrons and holes, and achieve efficient CO2 reduction. However, the preparation method of this invention is relatively complicated and requires three steps to synthesize Zn x Cd 1-x S / g-C3N4 heterojunction photocatalysts are not conducive to the precise control of the morphology and microstructure of the photocatalyst. Therefore, it is urgent to develop a method for preparing photocatalysts with high activity and good stability. Summary of the invention
[0005] In order to solve the above problems, the present invention provides an S-type heterojunction photocatalyst and its preparation method and application. The present invention uses a series of methods such as simple "thermal polycondensation technology" and "in-situ synthesis" to prepare a Zn with "killing two birds with one stone" characteristics. 0.5 Cd 0.5 S / g-C3N4, namely ZCS / g-C3N4S type heterojunction photocatalyst, is used to photocatalytically activate PDS under visible light to efficiently degrade ciprofloxacin.
[0006] The technical solution of the present invention is as follows:
[0007] One of the purposes of the present invention is to provide a method for preparing an S-type heterojunction photocatalyst, comprising the following steps:
[0008] S1: Using urea as raw material, pure g-C3N4 powder was prepared by thermal polycondensation method;
[0009] S2: 0.274 g of Zn(CH3COO)2·2H2O and 0.333 g of Cd(CH3COO)2·2H2O were placed in deionized water and stirred for 10-50 min, then 10 mL of Na2SO4·9H2O solution was added dropwise and stirred for 60-180 min, and then 30-300 mg of pure g-C3N4 powder obtained in step S1 was added, ultrasonicated for 60-180 min, and stirred for 30-150 min to obtain a suspension, and the suspension was transferred to a polytetrafluoroethylene-lined reactor, reacted at 130-220 ° C for 3-12 h, and cooled to room temperature with the box, washed with deionized water and anhydrous ethanol, and vacuum dried to obtain Zn with high activity and high stability. 0.5 Cd 0.5 S / g-C3N4 photocatalyst, that is, the S-type heterojunction photocatalyst.
[0010] Furthermore, the specific process of step S1 is:
[0011] S11: drying the urea in an oven, grinding it thoroughly, and calcining it in a muffle furnace at 500-600° C. for 180-360 min to obtain a precursor;
[0012] S12: After the precursor obtained in step S11 is cooled, it is fully ground, acidified with 0.5-3 mol / L nitric acid for 6-18 hours, washed with deionized water until the pH is 6-8, placed in an oven for drying, and finally fully ground to obtain a powder;
[0013] S13: The powder obtained in step S12 is placed in a muffle furnace at 500-600° C. and calcined for 180-360 min, washed three times with deionized water and anhydrous ethanol respectively, and then placed in an oven for drying to obtain pure g-C3N4 powder.
[0014] Furthermore, in step S11 and step S13, the heating rate of the muffle furnace is 2-5°C / min.
[0015] Furthermore, in step S11 to step S13, the temperature of the oven is 50-90° C., and the drying time is 12-36 hours.
[0016] Furthermore, in step S2, the Na2SO4·9H2O solution is obtained by dissolving 2.16162 g of Na2SO4·9H2O in 30 mL of deionized water.
[0017] Furthermore, in step S2, the vacuum drying is carried out at a temperature of 50-90°C and for a time of 12-36 hours.
[0018] A second object of the present invention is to provide an S-type heterojunction photocatalyst, wherein the S-type heterojunction photocatalyst is obtained by any of the above-mentioned preparation methods.
[0019] The third object of the present invention is to provide an application of an S-type heterojunction photocatalyst in the degradation of ciprofloxacin.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] 1. The present invention provides a method for preparing an S-type heterojunction photocatalyst, which uses a thermal polycondensation method to prepare a g-C3N4 photocatalyst, and then uses the highly uniform nitrogen ligands of g-C3N4 to provide abundant lone pair electrons to capture Zn in ZCS. 2+ and Cd 2 + , thereby forming a ZCS / g-C3N4 S-type heterojunction in one step by using the in-situ growth method. The process of preparing the ZCS / g-C3N4 S-type heterojunction by this method is simple, avoiding the problems of uneven interlayer bonding, weak bonding force, and poor photogenerated carrier transmission that may be caused by multiple transformations, thereby improving the structural stability and photocatalytic activity of the heterojunction.
[0022] 2. The S-type heterojunction photocatalyst provided by the present invention makes full use of the photogenerated electrons on the ZCS conduction band and the photogenerated holes on the g-C3N4 valence band, giving the S-type heterojunction the best redox ability, thereby improving its photocatalytic performance. The successful construction of the S-type heterojunction enables photogenerated electrons and photogenerated holes to be separated and migrated more effectively, and this separation process significantly enhances the efficiency of the photocatalytic reaction. The transfer of photogenerated electrons from the ZCS conduction band to g-C3N4 helps to improve the reactivity of the photocatalyst under illumination conditions, and this characteristic enables the photocatalyst to fully react under different environmental conditions, making it more flexible. In addition, the photogenerated carrier migration path effectively suppresses the photocorrosion phenomenon of ZCS, avoids the problem of catalyst collapse caused by the concentration of electrons and holes, and thus significantly improves the chemical stability of the photocatalyst and prolongs its service life. In summary, the successful construction of the S-type heterojunction of the present invention not only improves the photocatalytic activity, but also enhances the chemical stability of the photocatalyst, and has the characteristics of "killing two birds with one stone".
[0023] 3. The S-type heterojunction photocatalyst provided by the present invention has broad application prospects in the field of catalysis. It can be used for photocatalytic activation of PDS under visible light to efficiently degrade ciprofloxacin, and its degradation rate of ciprofloxacin is as high as over 90%, laying a solid foundation for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 An X-ray diffraction pattern of an S-type heterojunction photocatalyst provided by the present invention;
[0025] Figure 2 Transmission electron microscopy images of g-C3N4, ZCS and 1:2ZCS / g-C3N4 in the present invention;
[0026] Figure 3 The present invention shows the degradation rate and degradation reaction kinetics of ciprofloxacin under different reaction systems, the 1:2ZCS / g-C3N4+PDS system cycle experiment, and a schematic diagram comparing the rate and reaction kinetics of PDS degradation of organic pollutants by g-CN-based catalysts and sulfide-based catalysts under visible light. DETAILED DESCRIPTION
[0027] The following is in conjunction with the preferred embodiment and with reference to the attached Figure 1-3, the present invention is further described. The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values; for numerical ranges, the endpoint values of each range, the endpoint values of each range and individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed herein; the materials, reagents, etc. used in the following examples, unless otherwise specified, can be obtained from commercial channels; the experimental methods in the following examples, unless otherwise specified, are all conventional methods.
[0028] Example 1
[0029] This embodiment provides a method for preparing an S-type heterojunction photocatalyst, comprising the following steps:
[0030] S1: Using urea as raw material, pure g-C3N4 powder was prepared by thermal polycondensation method;
[0031] S11: drying urea in an oven at 80°C for 24 hours, grinding the urea thoroughly, and calcining the urea in a muffle furnace at 500°C for 240 minutes to obtain a precursor; the heating rate of the muffle furnace is 2.5°C / min;
[0032] S12: After the precursor obtained in step S11 is cooled, it is fully ground, acidified with 1 mol / L nitric acid for 12 h, washed with deionized water until the pH is 7, placed in an oven at 80° C. and dried for 24 h, and finally fully ground to obtain a powder;
[0033] S13: The powder obtained in step S12 is placed in a muffle furnace at 500°C and calcined for 240 min. The heating rate of the muffle furnace is 5°C / min. The powder is washed three times with deionized water and anhydrous ethanol respectively, and then placed in an oven at 80°C and dried for 12 hours to obtain pure g-C3N4 powder.
[0034] S2: 0.274 g of Zn(CH3COO)2·2H2O and 0.333 g of Cd(CH3COO)2·2H2O were placed in deionized water and stirred for 20 min, then 10 mL of Na2SO4·9H2O solution was added dropwise and stirred for 120 min, and then 40 mg of pure g-C3N4 powder obtained in step S1 was added. After ultrasonic treatment for 60 min, the suspension was stirred for 90 min to obtain a suspension, and the suspension was transferred to a polytetrafluoroethylene-lined reactor, reacted at 160°C for 4 h, and cooled to room temperature with the box, washed with deionized water and anhydrous ethanol, and vacuum dried at 80°C for 12 h to obtain a 1:5ZCS / g-C3N4 photocatalyst, i.e., the S-type heterojunction photocatalyst.
[0035] In step S2 of this embodiment, the Na2SO4·9H2O solution is obtained by dissolving 2.16162 g of Na2SO4·9H2O in 30 mL of deionized water.
[0036] Example 2
[0037] It is basically the same as Example 1, except that in step S2 of this example, 100 mg of pure g-C3N4 powder is added, and finally a 1:2ZCS / g-C3N4 photocatalyst is prepared.
[0038] Example 3
[0039] It is basically the same as Example 1, except that in step S2 of this example, 200 mg of pure g-C3N4 powder is added, and finally a 1:1 ZCS / g-C3N4 photocatalyst is prepared.
[0040] Example 4
[0041] This embodiment provides a method for preparing an S-type heterojunction photocatalyst, comprising the following steps:
[0042] S1: Using urea as raw material, pure g-C3N4 powder was prepared by thermal polycondensation method;
[0043] S11: drying urea in a 50°C oven for 36 hours, grinding the urea thoroughly, and calcining the urea in a muffle furnace at 550°C for 360 minutes to obtain a precursor; the heating rate of the muffle furnace is 2°C / min;
[0044] S12: After the precursor obtained in step S11 is cooled, it is fully ground, acidified with 0.5 mol / L nitric acid for 18 h, washed with deionized water until the pH is 6, placed in a 50° C. oven for drying for 36 h, and finally fully ground to obtain a powder;
[0045] S13: The powder obtained in step S12 is placed in a muffle furnace at 550°C and calcined for 360 min. The heating rate of the muffle furnace is 2.5°C / min. The powder is washed three times with deionized water and anhydrous ethanol respectively, and then placed in a 50°C oven and dried for 36 hours to obtain pure g-C3N4 powder.
[0046] S2: 0.274 g of Zn(CH3COO)2·2H2O and 0.333 g of Cd(CH3COO)2·2H2O were placed in deionized water and stirred for 10 min, then 10 mL of Na2SO4·9H2O solution was added dropwise and stirred for 180 min, and then 30 mg of pure g-C3N4 powder obtained in step S1 was added. After ultrasonic treatment for 100 min, the suspension was stirred for 30 min to obtain a suspension, and the suspension was transferred to a polytetrafluoroethylene-lined reactor, reacted at 130°C for 3 h, and cooled to room temperature with the box, washed with deionized water and anhydrous ethanol, and vacuum dried at 50°C for 18 h to obtain a ZCS / g-C3N4 photocatalyst, i.e., the S-type heterojunction photocatalyst.
[0047] In step S2 of this embodiment, the Na2SO4·9H2O solution is obtained by dissolving 2.16162 g of Na2SO4·9H2O in 30 mL of deionized water.
[0048] Example 5
[0049] This embodiment provides a method for preparing an S-type heterojunction photocatalyst, comprising the following steps:
[0050] S1: Using urea as raw material, pure g-C3N4 powder was prepared by thermal polycondensation method;
[0051] S11: drying urea in an oven at 90° C. for 12 h, grinding the urea thoroughly, and calcining the urea in a muffle furnace at 600° C. for 180 min to obtain a precursor; the heating rate of the muffle furnace is 5° C. / min;
[0052] S12: After the precursor obtained in step S11 is cooled, it is fully ground, acidified with 3 mol / L nitric acid for 6 h, washed with deionized water until the pH is 8, placed in a 90° C. oven for drying for 12 h, and finally fully ground to obtain a powder;
[0053] S13: The powder obtained in step S12 is placed in a muffle furnace at 600°C and calcined for 180 min. The heating rate of the muffle furnace is 2°C / min. The powder is washed three times with deionized water and anhydrous ethanol respectively, and then placed in a 90°C oven and dried for 24 hours to obtain pure g-C3N4 powder.
[0054] S2: 0.274 g of Zn(CH3COO)2·2H2O and 0.333 g of Cd(CH3COO)2·2H2O were placed in deionized water and stirred for 50 min, then 10 mL of Na2SO4·9H2O solution was added dropwise and stirred for 60 min, and then 300 mg of pure g-C3N4 powder obtained in step S1 was added. After ultrasonic treatment for 180 min, the suspension was stirred for 150 min to obtain a suspension, and the suspension was transferred to a polytetrafluoroethylene-lined reactor, reacted at 220°C for 12 h, and cooled to room temperature with the box, washed with deionized water and anhydrous ethanol, and vacuum dried at 90°C for 36 h to obtain a ZCS / g-C3N4 photocatalyst, i.e., the S-type heterojunction photocatalyst.
[0055] In step S2 of this embodiment, the Na2SO4·9H2O solution is obtained by dissolving 2.16162 g of Na2SO4·9H2O in 30 mL of deionized water.
[0056] Figure 1 The X-ray diffraction patterns of g-C3N4, ZCS and ZCS / g-C3N4 photocatalysts of different ratios prepared in Examples 1-3 of the present invention are shown in FIG. Figure 1 It can be seen that the corresponding diffraction peaks of single phase ZCS and g-C3N4 can be observed in the ZCS / g-C3N4 photocatalysts prepared in Examples 1-3, proving the successful synthesis of ZCS / g-C3N4 catalysts.
[0057] Figure 2 TEM images of g-C3N4, ZCS and 1:2ZCS / g-C3N4 prepared in Example 2 of the present invention, wherein: Figure 2 a is the transmission electron microscope image of g-C3N4, Figure 2 b is the transmission electron microscope image of ZCS. Figure 2 c is the transmission electron microscopy image of ZCS / g-C3N4. Figure 2 a It can be seen that g-C3N4 has a rough surface flake structure. Figure 2 b It can be seen that ZCS presents spherical nanoparticle morphology. Figure 2 c It can be seen that the present invention successfully loads ZCS on g-C3N4, indicating that the present invention successfully synthesized the ZCS / g-C3N4 catalyst.
[0058] Figure 3 The present invention is a graph of the degradation rate and degradation reaction kinetics of ciprofloxacin under different reaction systems, a 1:2ZCS / g-C3N4+PDS system cycle experiment, and a schematic diagram of the comparison of the rate and reaction kinetics of PDS degradation of organic pollutants by g-CN-based catalysts and sulfide-based catalysts activated under visible light. Figure 3It can be seen from a and 3b that the 1:2ZCS / g-C3N4 prepared in Example 2 of the present invention has the highest degradation efficiency for ciprofloxacin compared with other photocatalysts. After adding PDS, the degradation rate of ciprofloxacin is as high as 99.81%, and the reaction rate constant is 0.0461min -1 ;pass Figure 3 c It can be seen that under the same conditions, in the 4th and 5th cycles, the removal rate of ciprofloxacin by the 1:2ZCS / g-C3N4+PDS system was basically the same, and finally stabilized at about 91.22%, indicating that the 1:2ZCS / g-C3N4 photocatalyst has excellent chemical stability; Figure 3 d It can be seen that compared with other reported g-CN-based and sulfide-based photocatalysts, the 1:2ZCS / g-C3N4+PDS system has a very excellent degradation rate and reaction rate constant, indicating that the ZCS / g-C3N4 photocatalyst prepared in the present invention has the characteristic of "killing two birds with one stone".
[0059] The invention provides a method for preparing an S-type heterojunction photocatalyst, and the prepared S-type heterojunction photocatalyst has good redox ability and photocatalytic performance, high activity, good stability, and has the characteristics of "killing two birds with one stone". And through the degradation experiment of ciprofloxacin by activating PDS under visible light, it can be known that the degradation rate of ciprofloxacin is as high as 99.81% within 120 minutes, and after 5 cycles of experiments, the degradation rate of ciprofloxacin is still as high as more than 90% and remains stable. Compared with carbon nitride-based and sulfide-based catalysts in the prior art, the S-type heterojunction of the invention shows an excellent degradation rate.
[0060] The above is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several modifications and improvements without departing from the inventive concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A method for preparing an S-type heterojunction photocatalyst, characterized in that: The following steps are involved: S1: Using urea as raw material, pure g-C3N4 powder was prepared by thermal polycondensation method; S2: 0.274 g of Zn(CH3COO)2·2H2O and 0.333 g of Cd(CH3COO)2·2H2O were placed in deionized water and stirred for 10-50 min, then 10 mL of Na2SO4·9H2O solution was added dropwise and stirred for 60-180 min, and then 30-300 mg of pure g-C3N4 powder obtained in step S1 was added, ultrasonicated for 60-180 min, and stirred for 30-150 min to obtain a suspension, and the suspension was transferred to a polytetrafluoroethylene-lined reactor, reacted at 130-220 ° C for 3-12 h, and cooled to room temperature with the box, washed with deionized water and anhydrous ethanol, and vacuum dried to obtain Zn with high activity and high stability. 0.5 Cd 0.5 S / g-C3N4 photocatalyst, that is, the S-type heterojunction photocatalyst.
2. The method for preparing an S-type heterojunction photocatalyst according to claim 1, characterized in that: The specific process of step S1 is: S11: drying the urea in an oven, grinding it thoroughly, and calcining it in a muffle furnace at 500-600° C. for 180-360 min to obtain a precursor; S12: After the precursor obtained in step S11 is cooled, it is fully ground, acidified with 0.5-3 mol / L nitric acid for 6-18 hours, washed with deionized water until the pH is 6-8, placed in an oven for drying, and finally fully ground to obtain a powder; S13: The powder obtained in step S12 is placed in a muffle furnace at 500-600° C. and calcined for 180-360 min, washed three times with deionized water and anhydrous ethanol respectively, and then placed in an oven for drying to obtain pure g-C3N4 powder.
3. The method for preparing an S-type heterojunction photocatalyst according to claim 2, characterized in that: In step S11 and step S13, the heating rate of the muffle furnace is 2-5°C / min.
4. The method for preparing an S-type heterojunction photocatalyst according to claim 2, characterized in that: In step S11 to step S13, the temperature of the oven is 50-90° C., and the drying time is 12-36 hours.
5. The method for preparing an S-type heterojunction photocatalyst according to claim 1, characterized in that: In step S2, the Na2SO4·9H2O solution is obtained by dissolving 2.16162 g of Na2SO4·9H2O in 30 mL of deionized water.
6. The method for preparing an S-type heterojunction photocatalyst according to claim 1, characterized in that: In step S2, the vacuum drying is carried out at a temperature of 50-90°C and for a time of 12-36 hours.
7. An S-type heterojunction photocatalyst obtained according to the preparation method according to any one of claims 1 to 6.
8. Use of an S-type heterojunction photocatalyst according to claim 7 in the degradation of ciprofloxacin.
Citation Information
Patent Citations
Zinc-cadmium-sulfur solid solution / graphite-phase carbon nitride sheet composite S-shaped heterojunction photocatalyst, preparation and application thereof
CN115400776A
Cited By
Preparation method of composite nanoparticle photocatalyst
CN119926471A